Penggunaan Artificial Intelligence Animated Drawings Dalam Kegiatan Menggambar Sebagai Upaya Meningkatkan Kreativitas Anak Usia Dini - Pratiwi, Shelly; Zahra, Rahmi Rohimatul (LP2M STAI Al-Musaddadiyah Garut, 2025)
This research is motivated by the low level of creativity in drawing activities among early childhood students aged 5–6 years at RA Darul Ihsan Pinggirjati. Based on initial observations, 20% of the children (2 out of 10) were categorized as